Analysis of Heat Transfer Coefficient of Shell and Tube on Heat Exchanger Using Heat Transfer Research Inch (HTRI) Software - Alif Gita Arumsari; Petrus Junake Ginting (PT FORMOSA CENDEKIA GLOBAL, 2023)
The heat transfer process in the industrial world is the most important thing to pay attention to, especially in industrial equipment that works at high temperatures, one of the heat exchangers commonly used in the industrial world is a heat exchanger which is used to exchange heat between fluids of different temperatures. Therefore, it is necessary to pay attention to the performance of the heat exchanger. In the shell and tube type heat exchanger, apart from using baffles which aim to direct the flow on the shell side, it also aims to increase the rate of heat transfer that occurs between the working fluids by causing flow turbulence on the shell side. The results of this study are to obtain the heat transfer that occurs in the shell and tube in the heat exchanger, and to obtain the total heat transfer coefficient